Análisis del efecto del uso del suelo en las propiedades físicas de textura y pH de la parcela 17 del km 52 de la carretera Iquitos - Nauta - Nuñez Iñapi, Ramón (2020)
The development of this research work was carried out in the area of plot 17 of km 52 of the Iquitos - Nauta highway. Politically it is located in the department of Loreto, province of Maynas, San Juan Bautista district. The general objective was: To know the effect of soil use on the properties of texture and pH. The type of research of this study was descriptive and cross-sectional, which will know the state of the soil in the area under study, its use of the soil in the properties of texture and pH of plot 17 of km 52 of the Iquitos highway - Nauta”. The level of the research was detailed, because a total of 4 pits were carried out for the study within the plot, 2 pits in the primary forest and 2 pits in the 10 ha purma, which was the study population. Having as results: Calicata 1 primary forest, HO horizon with sandy clay loam textural class, Calicata 2 primary forest HB horizon with clay loam textural class, Calicata 3 agricultural plot OH horizon with clay loam textural class, Calicata 4 agricultural plot HB horizon with class clayey textual loam. The most abundant textual class in the study area was clay loam We must always take into account the range that determines the pH level (Hydrogen Potential) that the soils present.